Design, construction and validation of a minimum family unit production of the oyster mushroom at the center of renewable natural resources La Salada - Jaramillo Jaramillo, Gustavo Adolfo
A “minimum family unit production of the oyster mushroom” was designed and built. Several essential factors were taken into account such as: substrate for feeding the fungus as well as where it grows and develops. The objective was to standardize the production process controlling variables such as relative humidity and temperature, in order to achieve an acceptable biological efficiency according to the size and capacity of the unit. Therefore, aiming to provide healthy nutrition and food security to families, given the fact that this is a problem that worsens everyday without any fundamental solutions being contemplated. This model that aims at standardizing production, responds by small-scale production with affordable substrates and building materials. This project was conducted with trainees and instructors of the Natural Resources Area of the Center of Renewable Natural Resources La Salada. At present, there have been approximately six production cycles whose biological efficiency results were of 74.89%. This is a good production according to the substrate being used.